Intersecting Cultural Connections for Doctoral Persistence - Ruby Cain; Marjorie Treff (Adult Education Research Conference, 2009)
This Roundtable Discussion addresses the barrier of informal peer support system (where its absence is one of the cited barriers to doctoral persistence) via the theoretical framework of shared case stories. These case stories explore the experiences of two women who entered a doctoral program as returning adults, and the ways in which their separate stories intersected and became interdependent, supporting their persistence towards degree. The presenters will provide a theater style format to share their stories in four scenes.